2017
DOI: 10.1515/ling-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Why is children’s interpretation of doubly quantified sentences non-isomorphic?

Abstract: The initial hypothesis examined in this paper is that Hungarian preschoolers assign to sentences containing two numerical quantifiers and a distributivity marker the same isomorphic distributive interpretation as Hungarian adults do. This hypothesis is partially refuted by Experiment 1, a truth value judgement task, and Experiment 2, a forced choice task, which show that children can access distributive readings, however, they tend to accept both isomorphic and inverse scope. Experiment 3, an act-out task, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…That 4-6-year-old preschoolers can passively understand the distributive interpretation of doubly quantified sentences has been shown by previous literature (Musolino 2009; É. Kiss et al 2013;É. Kiss & Zétényi 2017).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…That 4-6-year-old preschoolers can passively understand the distributive interpretation of doubly quantified sentences has been shown by previous literature (Musolino 2009; É. Kiss et al 2013;É. Kiss & Zétényi 2017).…”
Section: Discussionsupporting
confidence: 57%
“…In a follow-up experiment, É. Kiss and Zétényi (2017) sought to answer the question of why Hungarian children's scope interpretation of doubly quantified sentences is not isomorphic, i.e., why they accept readings in which the scope order of quantifiers is the opposite of their linear order -even though non-isomorphic scope interpretation is absent from adult Hungarian. The results of an act-out task, as well as reaction time data indicated that the default reading of doubly quantified sentences for Hungarian preschoolers is the collective reading (also in the presence of the distributive clitic is), which they are willing to revise only under strong pragmatic pressure.…”
Section: Distributive Scope In Child Languagementioning
confidence: 99%
See 1 more Smart Citation